Pendampingan Pelatihan Menyulam Pada Remaja Panti Asuhan As-Salam Kota Pekanbaru - Misral Misral; Sri Rahmayanti; Siti Hanifa Sandri; Hendri Ali Ardi; Bakaruddin Bakaruddin; Norra Isnasia Rahayu; Jeki Algusri (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2020)
Embroidery crafts are one of the riches of Indonesian traditional culture. Embroidery is a decoration made on cloth with a sewing needle and thread. This embroidery training was attended by the As-Salam Orphanage young women. Community service activities in the field of embroidery skills training on the introduction of basic stitching to decorate fabrics to improve skills in the city of Pekanbaru. This is closely related to skills education that can be used in everyday life and entrepreneurship, namely decorating cloth. The method of implementation is through outreach and training approaches. The results of the activities felt by the training participants were that they could get to know the basics of embroidery skills and in the end they could have the skills to increase activity and productivity and it was hoped that it would increase family income. By providing the As-Salam Orphanage with knowledge and skills regarding basic stitching in embroidery, it can be concluded that in this Community Service activity, it is necessary to carry out repeated exercises to produce better work.